2014
DOI: 10.1103/physrevb.89.205420
|View full text |Cite
|
Sign up to set email alerts
|

Current-dependent periodicities of Si(553)-Au

Abstract: We investigate quasi one-dimensional atomic chains on Si (553)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The former is assigned to the dimerization of the Au double row along the steps 22 . An ab-initio calculation confirmed that the dimerized double row Au chain in the middle of the terrace and a single honeycomb-like graphitic strip of Si atoms at the step edge is energetically most favorable 22 , which is consistent with STM 9,12,13,15,23,24 and XRD 20 studies. DFT calculations taking into account spin polarization led to the most recent structure model 6 referred to as original in the following.…”
supporting
confidence: 69%
“…The former is assigned to the dimerization of the Au double row along the steps 22 . An ab-initio calculation confirmed that the dimerized double row Au chain in the middle of the terrace and a single honeycomb-like graphitic strip of Si atoms at the step edge is energetically most favorable 22 , which is consistent with STM 9,12,13,15,23,24 and XRD 20 studies. DFT calculations taking into account spin polarization led to the most recent structure model 6 referred to as original in the following.…”
supporting
confidence: 69%
“…In particular, it explains the observation of a metastable metallic phase at low temperature and the sensitivity of the critical temperature to the substrate doping. Grand canonical theories could explain other charge-donation related phenomena in atomic wires such as the reversible structural transitions in Au/Si(553) upon electron injection [48,49]. The present work suggests that variations of the substrate-induced chemical potential (e.g., with temperature or upon doping) is a key mechanism for understanding the realization of quasi-1D physics in atomic wires.…”
mentioning
confidence: 68%
“…The Si(553)-Au and Si(557)-Au surfaces are currently the focus of intensive study due to their ability to host onedimensional spin chains [7,34,[41][42][43]. Spins are reported to be located at the step edges and to order antiferromagnetically.…”
Section: Spin Ordermentioning
confidence: 99%